Penerapan Metode ELECTRE Dalam Pengambilan Keputusan Pemilihan Produk Unggulan Daerah - Leni Natalia Zulita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This Decision Support System aims to provide information, guide, provide predictions and direct information users to be able to make better decisions. Decision Support System is the implementation of decision-making theories that have been introduced by sciences such as Operation Research and Management Science, the only difference is that if first to find a solution to the problem at hand it must be calculated manually iteration (usually to find the minimum and maximum values ). At Dinas Perindustrian dan Perdagangan Kabupaten Seluma, each year it will select regional superior products from all products in each UKM in the Seluma Regency environment. However, the product evaluation process for each UKM is still done manually through the form provided by Dinas Perindustrian dan Perdagangan Kabupaten Seluma. The obstacle that often occurs is that Dinas Perindustrian dan Perdagangan Kabupaten Seluma requires a considerable amount of time in managing product data for each UKM, because every year there are UKM that are no longer active and there are new UKM